Pelatihan Cara Penggunaan Aplikasi Sikesal untuk Admin OPD Se-Kota Jambi - Kevin Kurniawansyah; Noneng Marthiawati; Hetty Rohayani; Hafiz Nugraha (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
At present, the Industrial Revolution 4.0 is not only happening in the industrial world but also in government agencies that apply technology to fulfill service needs to the community. The government is expected to answer all community needs by providing the best services based on information technology. One of them is the Jambi City Public Complaint Information System Applications or Online-Based Jambi City Community Complaint Application (SiKesal) is a form of information technology-based service application for incoming public complaints dominated by infrastructure, roads, drainage, cleanliness, street lights, clean water, and parking problems and about damage to be repaired. With the public complaint report, it will not be followed up by the relevant OPD admin, so it is necessary to train how to use the SiKesal application for OPD Admins in Jambi City so that each OPD admin knows what to do. On this basis, in the community service program (PkM) activities on this occasion, assistance in using the SiKesal application for OPD admins in the Jambi City which is one of the right solutions for the government to improve government services to the community so that public satisfaction and trust in the government can increase.